PENGARUH PERENCANAAN, PELAKSANAAN DAN PENGENDALIAN ANGGARAN TERHADAP KINERJA SATUAN KERJA PERANGKAT DAERAH (SKPD) KABUPATEN KEPULAUAN MENTAWAI - Amir Ahmari; Syamsul Amar (Program Studi Magister Manajemen, 2014)
This study aims to analyze the influence of Planning, Implementation and Control Budget to Performance Unit (SKPD) in the Mentawai Islands of West Sumatra, and see to what extent the efforts of SKPD make effective and efficient use of the budget. Samples was done by Multi Stage Sampling number 32 on education. Results of the study stated that: Budget planning is a positive and significant impact on the implementation of the budget, planning and implementation of the budget in a positive and significant effect on the control of the budget, Planning, Implementation and Control of the Budget affect positively and significantly related to performance on education in the Mentawai islands County Government, and There are direct and indirect influence of the Planning, Implementation and Control Budget is positive and significant impact on the performance of the Government on education in the Mentawai Islands. Keywords: Planning, Execution, Control, Performance, SKPD